Need for support or economic competition? Implicit associations with immigrants during the 2015 migrant crisis. (May 2018) - Johann, David; Thomas, Kathrin
How did the Austrian public think about immigrants at the peak of the 2015 migrant crisis? News media and policy makers suggested a cleavage in public opinion along the lines of humanitarian support and economic competition. We empirically disentangle these groups using a Single Category Implicit Association Test (SC-IAT). The data were collected by Project Implicit as a part of an online panel survey initiated by the Austrian National Election Study (AUTNES). The analyses reveal that Austrian citizens predominantly associate immigrants with the need for support. However, implicit associations also seem to vary depending on citizens' backgrounds and beliefs. The findings further indicate that implicit associations towards immigrants affect citizens' policy preferences.